Paparan Asap dalam Rumah, Hewan Peliharaan, Lingkungan Tempat Tinggal dan Sosial Ekonomi dengan Kejadian Asma Bronkial pada Anak - Astuti Erwin Hari, Naning Roni, Wibowo Trisno Agung (Berita Kedokteran Masyarakat (BKM), 2010)
Background: World Health Organization (WHO) estimates that 100 of 150 million world population suffer from asthma and the number increases 180,000 people a year. The prevalence of  bronchial asthma at District of Boyolali is increasing over years. The prevalence was 1.1% in 2005; 1.5% in 2006; 1.5% in 2007 and 2.55% in 2008.Objective: To identify association between exposure to smoke in the house, pets, living environment and social economic condition and the prevalence of asthma in children.Methods: The study was analytic observational with a case control study design. Samples were as many as 234 children (117 cases and 117 control) taken with consecutive sampling technique. Location of samples were Mojosongo Health Center, Cepogo Health Center and Banyudono Hospital. Control were taken from the same location, i.e. children diagnosed not having asthma. Analysis used Chi Square and multiple logistic  regression.Results: The result of bivariate analysis showed score of kitchen smoke exposure was OR=2.33 and p=0.00; cigarette smoke exposure was OR=1.87 and p=0.03. Contact with pets (cats/dogs) showed OR=2.33 and p=0.01. Social economic condition showed OR=2.13 and p=0.01. Living environment showed OR=1.62 and p=0.09. The result of multivariate analysis showed exposure to kitchen smoke was p=0.00 and OR=2.36; exposure to cigarette smoke was p=0.02 and OR=1.98; contact with pets (cats/dogs) p=0.02 and OR=2.23;social economic condition was p=0.01 and OR=2.27.Conclusion: Risk factors associated with the prevalence of bronchial asthma in children were exposure to kitchen smoke, cigarette smoke, contact with pets and social economic condition.Keywords:  bronchial asthma, risk factors, case control